A spatiotemporal analysis framework of the ecological security pattern based on the ecological “source–surface–corridor” and its implications - Zhang, Shuai; Chen, Yihao; Li, Jiwei; Ye, Qingqing; Chen, Weiqiang; Wang, Xiuli; Wei, Hejie; Jiang, Qinghu; Guo, Long (Frontiers in Ecology and Evolution, 2024)
A reasonable ecological security pattern can improve landscape connectivity, promote biological circulation, maintain ecological processes, and improve regional ecosystem service functions and human well-being. Accordingly, systematically and scientifically analyzing the spatiotemporal evolution characteristics of the regional ecological security pattern has essential theoretical and practical significance. This research proposed that the analysis framework of the ecological security pattern should include a complete system composed of ecological sources, resistance surfaces, and corridors. Thus, this research uses the ecological network method to systematically analyze the spatiotemporal evolution characteristics of the ecological security pattern in the Qinba–Dabie intersection zone in China, a complete natural ecological unit across administrative regions, from 2000 to 2020. Results revealed the following: (1) The distribution change law of the ecological sources in the study area was consistent with the distribution change law of their centrality. (2) In the northeast of the study area, the disappearance of the small ecological sources, which play a stepping stone role, led to a longer length and a weaker centrality of ecological corridors. (3) The resistance surface in the study area showed an overall growth trend, while the ecological corridor network showed an overall deterioration trend. Based on the results, this research suggests that the systematic analysis and targeted protection of ecological sources are the basis for maintaining the ecological security pattern, and targeted improvement of ecological resistance surface is the key to improving the ecological security pattern. Therefore, measures such as the protection of core ecological sources, the rational layout of ecological sources as stepping stones, and the improvement of resistance values at ecological key points should be paid attention to in the future.